Evaluating the Effectiveness of a Private College Workshop in Enhancing Journal Article Writing Skills: A Case Study of Academia International College - Bajracharya, Rajan Bilas; Shrestha, Rajesh Prasad; Khan, Hasim (Darul Yasin Al Sys, 2025)
Proficiency in academic writing, particularly in journal article composition, is a critical skill for researchers, educators, and postgraduate students in higher education. This study evaluates the effectiveness of a targeted writing workshop conducted by Academia International College, a private institution, designed to enhance journal article writing skills among faculty members and postgraduate students. Despite the increasing prevalence of such workshops, limited empirical evidence exists regarding their impact in private college contexts. Adopting a descriptive survey design, data were collected through structured questionnaires incorporating Likert-scale items across five key dimensions: content, delivery, engagement, learning outcomes, and logistics. The findings indicate that 93% of participants found the workshop content highly relevant, with practical applications for academic writing. The majority reported clear and engaging instruction supported by visuals and case-based examples, though some participants noted issues related to pacing. High engagement levels were observed, with 93.4% affirming that the workshop was interactive and well-timed. Regarding learning outcomes, 86.6% of respondents reported increased confidence in writing journal articles, while 93.3% expressed willingness to recommend the workshop to others. Feedback on logistics was generally positive, with minor suggestions for improving workshop materials. Overall, the workshop effectively addressed its objectives by delivering skill-based, context-specific training tailored to the needs of a private higher education audience. This study contributes to the discourse on academic writing pedagogy by highlighting the value of targeted professional development initiatives in under-researched private college environments.